Raman Scattering Enhancement by silver Nanostructures Prepared by Electrical Exploding Wire Technique - Moaen, FatimaFatimah Jumaah; Humud, Hammad R. (Iraqi Journal of Science, 2022)
This project aims to fabricate nanostructures (AgNPS) using the  electrical exploding wire (EEW) technique using Rhodamine 6G dye as the probe molecule, investigate the effect of AgNPS on the absorption spectra and surface-enhanced Raman scattering (SERS) activities, and advance  using porous silicon as an active substrate for surface-enhanced Raman scattering (SERS). X-Ray diffraction (XRD) was used to investigate the structural properties of the nanostructures (AgNPs). Field emission scanning electron microscopy (FE-SEM) was used to investigate surface morphology. A double beam UV-Vis Spectrophotometer was used to analyze the mixed R6G laser dye(of concentration 1x  M)  absorption spectra with the nanostructures AgNPS (of concentration 24x M). A sunshine Raman microscope device (the objective lens used was (50x)). was used to analyze R6G combined with nanostructures Raman spectra. All samples have shown SERS activity that increased with increasing the hot spots. The SERS enhancement factor for R6G dye(of 1x10-6 M concentration) when  mixed with (AgNPS) nanostructures has reached to(2.48 x 106) and the lowest detection limit reached to (1 x 10-14 M) at the wave number (1652 cm-1)  using excited laser source (λexc. = 532nm)